2002
DOI: 10.1093/annonc/mdf326
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 germline mutations in Sardinian breast cancer families and their implications for genetic counseling

Abstract: Identification of such features should address BC patients and their families to genetic counseling and BRCA1/2 mutational analysis. In addition, this is the first report of a detailed BRCA1/2 mutation screening in Sardinia, having immediate implications for the clinical management of BC families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
2
14
1
Order By: Relevance
“…Although it has been estimated that the percentage of hereditary breast carcinoma in Sardinia is comparable to that observed in other genetically homogeneous populations, 25,27 the prevalence of our BRCA2 founder mutation was lower than expected. Three BRCA1 founder mutations account for the vast majority of breast carcinoma families among Ashkenazi Jews, 22 and a single BRCA2 mutation accounts for nearly all breast-ovarian carcinoma families in Iceland.…”
Section: Discussioncontrasting
confidence: 51%
“…Although it has been estimated that the percentage of hereditary breast carcinoma in Sardinia is comparable to that observed in other genetically homogeneous populations, 25,27 the prevalence of our BRCA2 founder mutation was lower than expected. Three BRCA1 founder mutations account for the vast majority of breast carcinoma families among Ashkenazi Jews, 22 and a single BRCA2 mutation accounts for nearly all breast-ovarian carcinoma families in Iceland.…”
Section: Discussioncontrasting
confidence: 51%
“…In the present study, we found BRCA1/2 mutations in the 29.4% of BC/OC families from Barbagia, a proportion similar to that estimated in high-risk BC families from the northern part of Sardinia [14]. Four of five BRCA1/BRCA2 changes detected in this study were novel mutations not reported in the BIC database, pointing to the genetic peculiarity of the Barbagia population.…”
Section: Discussionsupporting
confidence: 85%
“…In Italy, a regional founder effect has been demonstrated for the mutation BRCA1 5083del19 and for the BRCA2 8765delAG which has been identified in the northern part of Sardinia [12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…In Sardinia, whose population is genetically homogeneous due to the fact that it is relatively isolated and with high rate of inbreeding, the contribution of BRCA mutations to the population incidence of breast cancer has been evaluated by our group in recent past years [23-25]. Three deleterious BRCA germline mutations have been observed in about 15% families and in about 3% non-familial breast cancer patients from North Sardinia ( BRCA2 mutations were the most prevalent BRCA sequence variations and a single variant, BRCA2-8765delAG , was the most recurrent mutation with a founder effect in our population) [23-25].…”
Section: Introductionmentioning
confidence: 99%